THE COMPETITIVENESS OF THE INTRA EU TRADE IN PROCESSED ANIMAL PRODUCTS IN SELECTED EU MEMBER STATES - Szubska - Włodarczyk, Natalia (European Scientific Journal, ESJ, 2014)
The main aim of paper is determine competitive position intra EU trade in processed animal products new member states of European Union. The method is quantitative analysis of the ex-post competitiveness indicators. The analysis was based on data from Eurostat and ComExt. The new EU member states have shown the least competitive among the processes animal products. The EU-15 countries are competitive in the agri - food. This is result greater technological and mechanization progress in agriculture.